Ontological (in)Security and African Pentecostalism in Ireland. Issue 5 (19th October 2016) - Maguire, Mark; Murphy, Fiona
ABSTRACT: The last number of years has seen the mushrooming of African Pentecostal churches, especially Prosperity Gospel churches, in the post-recession industrial landscapes of Ireland. This article aims to explore the growth of African Pentecostalism in Ireland from both the perspective of embodied and affective religious experience and the conditions for the possibility of those religious experiences. This article is based on several years of ethnographic research among African Pentecostals in Ireland. It attends especially to the sensorious forms of worship and the Jesus walks that Pentecostals organise to transform the Irish symbolic landscape. Drawing on recent anthropological theory, the article draws out the contradictions, doubts, boundaries and limitations perceived and lived in totalising Pentecostal discourses and practices. Here, we develop the concept of ontological (in)security in order to theorise these doubts and limitations as well as the power of contemporary Pentecostalism in late modernity.